Impact of Socioeconomic Status on Patients Supported With a Left Ventricular Assist Device: An Analysis of the UNOS Database (United Network for Organ Sharing). (October 2016) - Clerkin, Kevin J.; Garan, Arthur Reshad; Wayda, Brian; Givens, Raymond C.; Yuzefpolskaya, Melana; Nakagawa, Shunichi; Takeda, Koji; Takayama, Hiroo; Naka, Yoshifumi; Mancini, Donna M.; Colombo, Paolo C.; Topkara, Veli K.
Abstract : Background—: Low socioeconomic status (SES) is a known risk factor for heart failure, mortality among those with heart failure, and poor post heart transplant (HT) outcomes. This study sought to determine whether SES is associated with decreased waitlist survival while on left ventricular assist device (LVADs) support and after HT. Methods and Results—: A total of 3361 adult patients bridged to primary HT with an LVAD between May 2004 and April 2014 were identified in the UNOS database (United Network for Organ Sharing). SES was measured using the Agency for Healthcare Research and Quality SES index using data from the 2014 American Community Survey. In the study cohort, SES did not have an association with the combined end point of death or delisting on LVAD support ( P =0.30). In a cause-specific unadjusted model, those in the top (hazard ratio, 1.55; 95% confidence interval, 1.14–2.11; P =0.005) and second greatest SES quartile (hazard ratio 1.50; 95% confidence interval, 1.10–2.04; P =0.01) had an increased risk of death on device support compared with the lowest SES quartile. Adjusting for clinical risk factors mitigated the increased risk. There was no association between SES and complications. Post-HT survival, both crude and adjusted, was decreased for patients in the lowest quartile of SES index compared with all other SES quartiles. Conclusions—: Freedom from waitlist death or delisting was not affected by SES. Patients with a higher SES had an increased unadjusted risk of waitlist mortality during LVAD support, which was mitigated by adjusting for increased comorbid conditions. Low SES was associated with worse post-HT outcomes. Further study is needed to confirm and understand a differential effect of SES on post-transplant outcomes that was not seen during LVAD support before HT. Abstract : Supplemental Digital Content is available in the text.